Constitutional reform and its impact on TVET governance in Nepal: Second report in support of developing understanding and finding the way forward for federalising the TVET sector in Nepal - Ursula Renold; Thomas Bolli; Katherine Caves (ETH Zurich, KOF Swiss Economic Institute, 2018)
The present report should help the GoN to map out key elements to facilitate TVET federalisation. The report is intended to help stakeholders involved in Nepal's TVET sector understand the key steps to be taken towards federalisation.
Keywords: 330